SAAT BRITANNIA MENGUASAI NUSANTARA: KISAH PENJAJAHAN INGGRIS DI HINDIA BELANDA - Rosmaida, Rosmaida Sinaga; Asini, Asini Rohana Silaban; Klaudia, Klaudia Marsanda; Putra, Putra Rabial Sibarani; Rosi, Rosi Daniela Sinambela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the short period of British colonial rule in the Dutch East Indies, especially in Java from 1811 to 1816, which began with the Tuntang Agreement and ended with the return of power to the Dutch. The problem addressed in this research is how British policies under Thomas Stamford Raffles influenced the social, economic, and political structure of Javanese society. The purpose of this study is to explain the characteristics of British colonialism in comparison to the Dutch and to analyze its impacts as a transitional phase in Indonesian colonial history. The method used is a library research with a descriptivequalitative approach, relying on scientific journal articles as the main source. The results of this study show that British rule introduced reforms such as the land rent system, the abolition of forced labor, and indirect rule through local elites. However, these policies were not fully successful due to the lack of administrative capacity and the unpreparedness of Javanese society to adapt to a money-based economy. The conclusion is that British colonialism in Java, although short-lived, left ambivalent impacts: on the one hand, it brought liberal reforms and modernization, but on the other hand, it still burdened the people and strengthened elite dominance. This period can be regarded as an important transitional phase before the implementation of the Dutch Cultuurstelsel in 1830.